Ортез на гомілковостопний суглоб-стопу з керуванням силами реакції опори для осіб, які не можуть самостійно замикати колінний суглоб - Баєв, П. О.; Півоваров, В. В.; Бобошко, Р. О.; Дацок, О. М. (ХНУРЕ, 2019)
In theses the description of a new designed construction of an ankle-foot orthosis with ground reaction forces control is given. It is marked, that the feature of the construction is the presence of the opening anterior valve which rigidly fixes a knee joint in extension in single support phase. The biomechanical principle of action of the designed orthosis is considered which implies that in the midstance the forefoot contacts to a surface and creates the knee extension moment due to inclusion of a knee anteriorly.
Keywords: ортез; інсульт; гомілковостопний суглоб-стопа